(untitled) (Indian Journal of Public Health Research & Development, 2020)
Objectives: The objectives of the study were to identify the consumption rate of sweetened beverages among adolescents, to identify the factors influencing the consumption of sweetened beverages and to find out the association between consumption rate and the selected demographic variables. Method: A descriptive survey was conducted among 100 adolescents from Pre University Colleges at Mangaluru from august to January 2019. Probability simpler and om technique was used in the study to select the sample. The criteria checklist was used as the tool for finding the consumption rate and factors influencing consumption rate. Result: The result showed that 69% percentages oft head ole scents were extensively consuming sweetened beverages and the factors that have an effect on the se consumption rates are peer pressure, encouragement of the family, advertisements, availability, taste, color and climatic condition. The study also shows that there no association between the consumption rate and the selected demographic variables. Conclusion: Increased consumption rate of sweetened beverages among adolescents was associated with taste, easy availability of sweetened beverages, peer pressure, climatic conditions etc.